ISTILAH DALAM FORUM JUAL-BELI DARING DI MEDIA SOSIAL FACEBOOK - R. Hery Budhiono (tuahtalino, 2020)
Online trading is spreading world wide nowadays. It becomes such a trend in this information technology era. Traditional way of trading looks old-fashioned when it is compared with its new model. This bombing phenomena of online trading encourages the rise of new restricted codes used by its participants. It has a certain typical characterictics. This work tries to indentify dan define terms used within contextually. It is a qualitative descriptive research. The data come from two dominant grups in Facebook, Indonesian Casuals and Clobber Casual group. The writer found that there are many foreign terms used by the participants of the whole groups. For the community, these codes differentiate them from any other communities.